Health Seeking Behavior, Cost of Illness and Quality of Life of Patients with COPD among 35 Years (Global Journal of Medical Research, 2019)
Background: COPD is the 4th leading cause of death worldwide and predicted to be third by 2030. In India, COPD accounts for 7% of mortality and 3% DALYs loss. Objective: The study undertaken to assess the health seeking behaviour and cost of illness of COPD and the influence of severity of the disease over the cost and the quality of life. Materials and Methods: The study conducted in 115 patients aged 35 years and above, a rural population of Gurugram, Haryana. Cost of illness (direct and indirect costs) was calculated in Indian rupees from the expenditures of the hospital visits, pharmacotherapy, oxygen therapy, biochemical investigations, diagnostic procedures, physiotherapy and hospitalization due to acute exacerbations by patient interview and review of patient#x2019;s case history, medical and billing records. Quality of life of patients in Stage III and Stage IV COPD was estimated using St. George#x2019;s Respiratory Questionnaire (SGRQ) score. Data collected on structured schedule
Keywords: COPD; health behavior; medical cost; quality of life